Penguatan Moderasi Beragama dalam Perspektif Politik di Kabupaten Kotawaringin Timur - Gofur, Abdul; Wahid, Abdul; Napisah, Nur (Journal of Moral and Civic Education, 2023)
The aim of this research is to describe strengthening religious moderation through political education in East Kotawaringin Regency. This strengthening was carried out through two activities by the National and Political Unity Agency (Kesbangpol) and the Religious Harmony Forum (FKUB). This type of research uses qualitative research with a qualitative descriptive approach. Data collection techniques use interviews and documentation. The data analysis technique goes through stages in the form of: data collection, data reduction, data presentation and drawing conclusions. The research results showed that strengthening religious moderation in East Kotawaringin Regency was carried out through collaboration between government and non-government institutions, elements of society and community organizations (ormas). The emphasis is on instilling the values of tolerance in politics through; respecting each individual's choice in elections, avoiding fraudulent practices or being involved in money politics, the practice of exercising the right to vote, associating and assembling without any intervention from any party, equal rights for every citizen in politics and changing the mental attitude of the younger generation . The development of the concept of religious moderation in this city needs to be reviewed again regarding its effectiveness in society.